2020
DOI: 10.1080/19420862.2020.1758291
|View full text |Cite
|
Sign up to set email alerts
|

Human-likeness of antibody biologics determined by back-translation and comparison with large antibody variable gene repertoires

Abstract: The antibody (Ab) germline gene rearrangement of variable (V), diversity (D), and joining (J) gene segments, as well as somatic hypermutation, give rise to the human Ab variable gene sequence repertoire. It is common to characterize single nucleotide frequencies of the variable region by alignment to species-specific wildtype germline genes. The increasing application of next-generation sequencing to immune repertoire studies has led to the compilation of increasing large adaptive immunome receptor repertoire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…developed a computational method that maps the sequence of a given antibody onto human B-cell repertoires comprising 326 million sequences of human antibodies. 141 Chin et al . built a machine learning-based predictive model that distinguishes human antibody sequences from non-human ones, which was trained on large-scale repertoire dataset.…”
Section: Applications Of Biopharmaceutical Informaticsmentioning
confidence: 99%
“…developed a computational method that maps the sequence of a given antibody onto human B-cell repertoires comprising 326 million sequences of human antibodies. 141 Chin et al . built a machine learning-based predictive model that distinguishes human antibody sequences from non-human ones, which was trained on large-scale repertoire dataset.…”
Section: Applications Of Biopharmaceutical Informaticsmentioning
confidence: 99%
“…Existing methods based on homology [9][10] are interpretable but lack granularity since they only provide a single score for each chain. Moreover, these underperformed in our analysis compared to more recent approaches such as IgReconstruct [17], which could be attributed to the modest size of their reference sequence libraries. Interestingly, Germline content, a baseline method we implemented based only on percent sequence identity to nearest human germline performed comparably to recent methods while providing both an interpretable and granular score.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, it was shown that developability properties of natural human antibodies are comparable with those of clinical mAbs [16]. In IgReconstruct [17], the OAS database was used to construct a back-translation method producing human-like DNA and evaluating humanness based on positional nucleotide frequency. Most recently, OAS was used in Hu-mAb [18] to train a random-forestbased humanness score used as an optimization criterion for iterative humanization.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of NGS increased the antibody sequence samples from the order of magnitude thousands to millions. Improved positional frequencies were created based on such data [ 103 , 104 ].…”
Section: Developability—deimmunization Using Large-scale Ngs Data And...mentioning
confidence: 99%